Analyzing Students' Numeracy Skills in Personal Context Problems: A Study of the Minimum Competency Assessment (MCA) - Julia Noviani; Septia Wahyuni; Anisah Khairani; Mahfudzah Ulfa (Universitas Pendidikan Mandalika, 2025)
This study addresses the gap in understanding how personal context influences students' numeracy skills, particularly in the context of the Minimum Competency Assessment (MCA) in Indonesia. The research problem centers on the challenge of engaging students with numeracy tasks that are not only mathematically relevant but also relatable to their personal experiences. While the MCA assesses mathematical reasoning and problem-solving, students often struggle to apply these skills to real-world scenarios, particularly when the context of the problems is unfamiliar or disconnected from their daily lives. This study aims to analyze the numeracy skills of eighth-grade students in solving problems with a personal context within the Minimum Competency Assessment (MCA). The study employed a mixed-methods design, integrating both quantitative and qualitative data. Quantitative data were analyzed using content validity analysis (Aiken's V) and inter-rater reliability (Cohen's Kappa) to assess the validity and consistency of the MCA questions. Descriptive statistics were used to analyze the students' numeracy scores. For qualitative analysis, semi-structured interviews were conducted to explore students' reasoning and problem-solving strategies. The triangulation of data from the MCA tests and interviews provided a comprehensive understanding of how students engaged with mathematical problems and applied their numeracy skills in real-world contexts. A total of 17 eighth-grade students were selected, and three students from each numeracy category; high, medium, and low were chosen using a categorization method based on standard deviation. Results showed that students with high numeracy abilities demonstrated effective problem-solving and reasoning skills, while students with medium and low numeracy abilities struggled with complex problems and real-world applications. The study suggests that while personal context can enhance student engagement, its effectiveness depends on a solid foundation in numeracy skills. The findings recommend a balanced approach in teaching, strengthening foundational skills alongside contextualized learning. In conclusion, while the personal context in MCA increases student engagement and relevance, particularly among high-performing students, its effectiveness is contingent on a solid foundation in basic numeracy skills. A balanced approach that strengthens basic numeracy skills while incorporating personal contexts is necessary to foster critical thinking and effective application of mathematics across all ability levels.